Semiotika Iklan TIKI - Wiwik Sundari (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2012)
Semiotics is the study of sign. Sign can be word, gesture, traffic light, flag, and so on. One of the fields which is closely related to semiotics is advertising. Through advertisement, producers send messages for their product strength to consumers. Those messages are conveyed through advertisement, producers, send messages for their product strength to consumers. Those messages are conveyed through various kinds of signs either in the form of language, picture, caption, icon, index, or symbol. Advertisement is also a medium consisting of many kinds of signs. Those signs are used to reveal the strength of product which is eventually expected to be able to influence consumers to use the service. There is communicative exchange in Tiki advertisement between sender and receiver. Sender (advertisement conceptor/maker) of this advertisement makes good use of reward polluter style, that is, persuading consumers to try a service of Tiki. To draw consumers' interest to use the service, Tiki advertisement uses imperative sentences as well as praising words in its product.